2021
DOI: 10.2478/bjes-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

A Different Approach to the Evaluation of Smart Cities’ Indicators

Abstract: The article aims to propose a different approach to assessing smart cities which combines some commonly used indicators with several new ones in line with the concept of sustainability. The aspect of sustainable development as an essential driver for the smart city and the combination of indicators for sustainable and smart city concepts have been analysed fragmentarily so far. There are many different approaches to evaluate the indicators of city smartness; however, very little attention is paid to the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The application of the proposed conceptual framework vital to be included as smart eco-city aspects, to ensure information protection (contributing to T06).  Performance of smart eco-cities measurements [20] and evaluation should be established through new metrics derived from smart eco-cities indices (contributing to all the indicators).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the proposed conceptual framework vital to be included as smart eco-city aspects, to ensure information protection (contributing to T06).  Performance of smart eco-cities measurements [20] and evaluation should be established through new metrics derived from smart eco-cities indices (contributing to all the indicators).…”
Section: Discussionmentioning
confidence: 99%
“…known as soft infrastructures and human resources [18]. Moreover, there is a European approach that recognizes a smart city as a city with a good future in terms of six main pillars namely; smart economy, smart people, smart environment, smart living, smart mobility, and smart governance [19], [20].…”
Section: Smart Citiesmentioning
confidence: 99%
“…Figure 6, below, shows the final combined ranking with a proposed list of indicators under each dimension, allowing for generating a specific rubric for measuring elements such as SSC deployment, progress, and compliance. [16,58,60,61,64,66,69,[76][77][78]113,114].…”
Section: Combined Ranking Of the Ssc Dimensionsmentioning
confidence: 99%
“…and revealed that cities cannot be truly smart without being sustainable in the first place [30]. On a higher level, sustainability or its varied forms can become key indicators for measuring cities' smartness, such as conservation of natural resources [31] and environment impact from energy use [32]. Smart cities are designed to promote sustainability, ensuring access to essential human development and well-being [30].…”
Section: Theoretical Backgroundmentioning
confidence: 99%